ANALYSIS OF THE INFLUENCE OF THE UNITED STATES (US) AND CHINA ECONOMIC POLICY UNCERTAINTY (EPU) ON STOCK VOLATILITY IN 5 ASEAN COUNTRIES BEFORE AND DURING COVID-19 - Khaeru Nisa Aulia Urakhma; Harjum Muharram (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of this study is to analyze the effect of Economic Policy Uncerianty (EPU) on the volatility of the ASEAN 5 stock market. The method used in this study is a quantitative research method using a regression model and Generalized Autoregressive Conditional Heteroscedasticity (GARCH). The sample of this research is 5 ASEAN countries, namely Indonesia, Malaysia, Singapore, Thailand and the Philippines. The results showed that the United States EPU found a positive effect on the volatility of the stock market indexes of Malaysia, Singapore, and Thailand while Indonesia and the Philippines did not have a positive effect in the period before and during COVID-19. China's EPU has no effect on the volatility of the ASEAN 5 stock market indexes before and during COVID-19. This study also finds that the volatility of the previous period affects the volatility of the current ASEAN 5 stock market index before and during COVID-19. Keywords: Economic Policy Uncertainty (EPU), GARCH, Volatility of stock market indices, COVID-19 pandemic